Procoagulant Activity of T Lymphoblastoid Cells in Extrinsic and Intrinsic Coagulation Systems - Barrowcliffe, T W; Marshall, Dianne E; Trickett, Lynne P; Hubbard, A R; Gray, Elaine; Thorpe, R (Thrombosis and Haemostasis, 1989)
We have measured the procoagulant activity (PCA) of four T lymphoblastoid cell lines (Jurkat, CEM, HSB-2 and Molt 4) as well as normal peripheral blood T lymphocytes, before and after stimulation with phytohaemagglutinin (PHA), using clotting and amidolytic methods.Of the four cell lines only one, Jurkat, gave enhanced PCA after stimulation with PH A. This activity was shown to be tissue factor-like by its dependence on factor VII in plasma and in an amidolytic assay with purified factors VII and X. Jurkat was also the only one of the four cell lines to secrete interleukin-2. All four cell lines promoted the generation of large amounts of thrombin in platelet-free plasma in glass tubes. This activity was dependent on the presence of plasma factor VIII, and was probably due to phospholipids in the cell membranes. Normal T lymphocytes gave intrinsic PCA in the thrombin generation test which was only 15% of that of the lymphoma cells.These results show that some T lymphocytes can develop PCA in both intrinsic and extrinsic systems and this should be taken into account in studies of the PCA of mixed leukocyte populations.
Keywords: Leukocytes; Tissue factor; Procoagulant activity